NPL Pengaruh Non Performing Loan (NPL) dan Loan to Deposit Ratio Terhadap Return On Assets (ROA) Pada PT Bank Pembangunan Daerah Papua - Toatubun, Helmi; Rahmi, Rahmi (Universitas Putera Batam, 2024)
This study aims to analyze the effect of Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in PT Bank Pembangunan Daerah Papua. The analysis method used is multiple linear regression. The results of the analysis show that partially, NPLs have a negative and significant effect on ROA, which means that the higher the level of non-performing loans, the lower the bank's profitability level. Meanwhile, LDR had a positive but insignificant effect on ROA, indicating that although increasing LDR may increase profitability, the effect is not strong enough to significantly affect ROA. However, simultaneously, the NPL and LDR variables had a positive and significant effect on ROA, which suggests that the two variables, when considered together, can make a significant contribution to the bank's financial performance.